Knowledge, Peer Support and Adherence to Blood Supplement Tablet Use Among Adolescent Girls - Kharisma Kusuma Nagari; Aloysia Ispriantari; Shinta Wahyusari (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Anemia among adolescent girls remains a serious public health concern in Indonesia, with prevalence of 18% reported in 2023. Although the government has implemented blood supplementation programs, adherence to tablet consumption remains a challenge. Various Although several studies have examined factors associated with adherence to blood supplement tablet consumption, adherence among adolescent girls remains low, indicating the need for further research related to factors associated with adherence to blood supplement consumption. This study aimed to examine the relationship between knowledge and peer support on compliance with blood supplement tablet consumption among adolescent girls. A cross-sectional design was employed, using total sampling of 184 tenth-grade female students from Senior High School 1 Kademangan, Blitar Regency. Data were collected via validated questionnaires administered through Google Forms. Data analysis was conducted using the Chi-Square test, with a significance level set at p < 0.05. Results showed that the majority of subjects had insufficient knowledge about blood supplement tablets (51%), low peer support (75%), and poor adherence with consumption (91%). Statistical analysis revealed significant associations between knowledge and adherence (p = 0.020) as well as between peer support and adherence (p = 0.044). These findings underscore the importance of comprehensive health education and peer-led empowerment initiatives in improving adherence to blood supplement programs among adolescent girls.